2014
DOI: 10.1364/jot.81.000164
|View full text |Cite
|
Sign up to set email alerts
|

Smoothing evolution model for computer controlled optical surfacing

Abstract: A polishing pad can smooth out mid-to-high spatial frequency errors automatically due to its rigidity and modeling of the smoothing effect is important. The relationship between surface error and polishing time is built here based on the Bridging model and Preston's equation. A series of smoothing experiments using pitch tools under different motion manners were performed and the results verified exponential decay between surface error and smoothing time. At the same time, parameters describing smoothing effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…However, the k defined in this model neglects the instantaneous property. It has been shown that the MSF errors decay exponentially with time during smoothing [14]. Unfortunately, the smoothing rate is not yet well defined.…”
Section: Rc Lap and Parametric Smoothing Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the k defined in this model neglects the instantaneous property. It has been shown that the MSF errors decay exponentially with time during smoothing [14]. Unfortunately, the smoothing rate is not yet well defined.…”
Section: Rc Lap and Parametric Smoothing Modelmentioning
confidence: 99%
“…Later, Kim et al introduced a parametric smoothing model based on the simplified Bridging model to describe smoothing effects [12]; this parametric smoothing model was further verified by Shu et al using a correlation-based model [13]. Shu et al also noted that the model presented by Kim et al neglected the instantaneous property and therefore constructed a new model based on the Bridging model [14]. This new model discloses the exponential decay of the MSF errors with time during smoothing.…”
Section: Introductionmentioning
confidence: 97%
“…There is no analytical expression for θ in Equation 10. The value of θ should be calculated by numerical method and then the value of ρ can be obtained.…”
Section: Modeling Of Archimedean Spiral Polishing Pathmentioning
confidence: 99%
“…In recent years, there were efforts to develop versatile polishing processes in order to achieve high accuracy. The current polishing methods mainly include electrochemical polishing [2], magnetorheological fluid polishing [3,4], plasma polishing [5,6], ultrasonic polishing [7,8] and *Correspondence: libing.sgs@hit.edu.cn 1 Shenzhen Graduate School, Harbin Institute of Technology, Shenzhen University Town, Xili, 518055 Shenzhen, China Full list of author information is available at the end of the article computer-controlled mechanical polishing [9,10]. Nowadays, a lot of freeform components are still produced by final manual polishing.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the smoothing time during the polishing process, the evolution of surface errors was revealed and an exponentially decreasing function image was obtained [13]. And by comparing the different polishing pad movements, it was pointed out that the smoothing curve under the double planetary motion drops faster and the smoothing limit value is smaller, indicating that the double planetary motion polishing pad has better smoothing effect.…”
Section: Introductionmentioning
confidence: 98%